REVISITING ANALYSIS OF THE ROOT CAUSES ON FINANCIAL CRISIS IN ISLAMIC PERSPECTIVE - Luik, Mega T.R.; Fatoni, Ahlis (Journal of Islamic Monetary Economics and Finance, 2018)
Steady financial system stability is important in an economy. The financial crisis showed a constantly recurring problem that has not been resolved completely. Macroprudential policy which became the term savior after the subprime mortgage crisis was essentially a temporary not eliminate the root causes of the problems of the financial crisis. This study attempts to revise the root causes of the financial crisis in the perspective of Islam by using three approaches namely Vector Error Correction Model (VECM), Error Correction Model (ECM), and Distributed-Lag Autoregressive (ARDL). The result of this study that the consistence of ribâ (interest rate) variable as the main factor of crisis; ribâ increases the inflation and decreases the growth. The IRF (impluse response function) result and FEVD (forcast error varian decomposition) show 21.87% interest rate (INT) increases the inflation and decreases the growth by 9.5%, while profit-loss sharing (PLS) variable contributes to decreases the inflation by 0.02% and increases the growth by 0.61%, reciprocally with ECM approach that interest rate (INT) has positive effect to inflation and  negative effect to growth (financial crisis) vice versa PLS sicnificantly has negative effect to inflation and positive effect to grwoth, whereas ARDL approach shows that PLS increases the grwoth at long and short run but also increases the inflation at long run. Another conventional variabels consistantly contribut to financial crisis acording to all aproachs; volatile food (VFP) and administred price (ADM).